SENSIBILIDAD Y ESPECIFICIDAD DEL INDICE DE KROGH POULSEN EN EL DIAGNOSTICO DE LOS TRANSTORNOS TEMPOROMANDIBULARES - Cornejo Salazar, José Luis (1999)
A clinical investigation has been realized with the purpose of testing the sensibity and the specificity of Krogh Poulsen muscle exploration, on 80 individuals of both sexes bethwen 15 and 50 years of age were randomy selected that assisted to the dental service of Guillermo Almenara Hospital. Procedures to diagnoses temporomandibular disorders were appied, refered by the Krogt Poulsen muscle exploration and the Helkimo's index. The present study constituted the "gold standard" Validity formula based on the table of four boxes were applied. Parametric test of Z scores of were applied and cualitative variables were proved by the chi square test. The results indicated a sensitivity of 78% and a specifity of 100% on the Krogh Poulsen muscle exploration. This showed it is major utility in the Diagnoses of healty individuals. The most frecuent distintive signs were the minimization in the opening and closing and pain of TMJ.